2019
DOI: 10.5114/ada.2018.80615
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of dermatomycoses in southwest Poland, years 2011–2016

Abstract: IntroductionSuperficial mycosis is one of the most common diseases worldwide, however its epidemiology is changing over time.AimTo present epidemiological data of the skin fungal infections diagnosed in the years 2011–2016 in Lower Silesia.Material and methodsA total of 11 004 patients with a clinically suspected superficial mycosis were investigated. Skin scrapings, nail clippings and plucked hair were examined with a direct microscopy, Wood’s lamp and culture. Particular species were identified via polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 18 publications
0
20
1
Order By: Relevance
“…The top three pathogenic fungi of superficial mycosis isolated in the 10 years from 2008 to 2018 were Trichophyton rubrum , Trichophyton mentagrophytes and Candida . The results were different from the previous research results in Jilin ( 17 ). However, Trichophyton rubrum is still the first pathogen species, and most studies in China and worldwide also show that Trichophyton rubrum is the primary pathogen of superficial mycosis ( 18-21 ).…”
Section: Discussioncontrasting
confidence: 99%
“…The top three pathogenic fungi of superficial mycosis isolated in the 10 years from 2008 to 2018 were Trichophyton rubrum , Trichophyton mentagrophytes and Candida . The results were different from the previous research results in Jilin ( 17 ). However, Trichophyton rubrum is still the first pathogen species, and most studies in China and worldwide also show that Trichophyton rubrum is the primary pathogen of superficial mycosis ( 18-21 ).…”
Section: Discussioncontrasting
confidence: 99%
“…We also demonstrated that there are significant differences between children and adults. We compared our data with results from a survey conducted in our region in the general population in 2011–2016 [ 29 ]. T. rubrum was also the most prevalent causative agent detected in 71.75% of cases, followed by T. tonsurans observed in 16.77% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at this time, T rubrum gained the leading position among anthropophilic species with a share of 70%, followed by T interdigitale (0.6%–34%) and E floccosum (19%–15%). Recently, a single‐centre study on superficial mycoses in Lower Silesia (Poland) conducted between 2011 and 2016 showed that T rubrum represented 80.69% dermatophytes isolated from toenails and 72% isolated from feet, whereas the second was T tonsurans (14% and 22%, respectively) 10 . The global epidemiology of dermatophytosis was extensively reviewed by other authors 4,7,11 .…”
Section: Aetiologic Factors and Epidemiology Of Tinea Pedis And Toenail Onychomycosismentioning
confidence: 99%
“…Recently, a single-centre study on superficial mycoses in Lower Silesia (Poland) conducted between 2011 and 2016 showed that T rubrum represented 80.69% dermatophytes isolated from toenails and 72% isolated from feet, whereas the second was T tonsurans (14% and 22%, respectively). 10 The global epidemiology of dermatophytosis was extensively reviewed by other authors. 4,7,11 Therefore, this work presents data from selected papers published in the last decade (Table 1).…”
Section: Ae Ti Olog I C Fac Tor S and Epidemi Ology Of Tine A Ped Is And Toenail Onychomycos Ismentioning
confidence: 99%